Students’ Perception towards the Use of Edmodo in Online-Based English Learning Class at Universitas Fajar - Tamrin, Andi Febriana (Celt: A Journal of Culture, English Language Teaching & Literature, 2019)
Online-based learning or lecture is deemed as a new learning methodology among academics in this present era. This method involves a learning process in which lecturers and students could undergo lectures or courses without being present in the classroom.  One of the online applications that supports this method is Edmodo. This study aims to obtain data about the perception of students regarding the use of Edmodo in English language classes at Universitas Fajar. The method used in this study is descriptive study. The result showed that although it has drawbacks, Edmodo is considered as one of the most effective tools in supporting the learning process.